Aspek Spiritualitas dalam Pemenuhan Kebutuhan Spiritual Pasien - Hermin Husaeni; Abdul Haris (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background; Nurses as health professionals have the greatest opportunity to provide health services, especially comprehensive nursing services / care by helping clients meet their basic holistic needs. Method; descriptive analytic crosssectional method with purposive sampling technique sampling. Data analysis used univariate and bivariate using statistical tests with a significance level of 0.05 and processed electronically using the SPSS 21 program. Results; The statistical test obtained the value of ρ = 0.034 <α = 0.05, there is a relationship between the application of the spirituality aspects of nurses and the fulfillment of the spiritual needs of patients. Conclusion; There is a relationship between the application of the spirituality aspects of nurses with the fulfillment of spiritual needs for inpatients. There needs to be a strategy in improving health services, especially in applying the spiritual needs of the patient.